Digital-Based Public Governance at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Sidenreng Rappang Regency - Vera Juniyengsi; Abdul Jabbar; Herman (Journal of Governance and Social Policy, 2026)
This study analyzes digital-based public governance practices at the DPMPTSP of Sidenreng Rappang Regency and their contribution to good governance principles. A qualitative approach was employed using interviews, observation, and documentation, with thematic data analysis assisted by NVivo 12 software. The findings indicate that digitalization predominantly strengthens transparency and accountability through the OSS system, websites, social media, and complaint mechanisms. However, public digital participation remains uneven, evidenced by the dominance of face-to-face services (75%) compared to online services (25%). Supporting factors include clear regulations, leadership commitment, internal coordination, and human resource capacity building. Conversely, the main obstacles are the public's low digital literacy, a preference for manual services, and technical constraints in system integration. In conclusion, digitalization at the DPMPTSP has significantly strengthened administrative governance but has not yet fully achieved an inclusive and strategic governance transformation for the wider community.